The Iron-Inflammation Axis in Early-Stage Triple-Negative Breast Cancer - Duan, Fangfang; Zhong, Muyi; Ye, Jinhui; Wang, Li; Jiang, Chang; Yuan, Zhongyu; Bi, Xiwen; Huang, Jiajia (Frontiers in Cell and Developmental Biology, 2022)
The iron-related homeostasis and inflammatory biomarker have been identified as prognostic factors for cancers. We aimed to explore the prognostic value of a novel comprehensive biomarker, the iron-monocyte-to-lymphocyte ratio (IronMLR) score, in patients with early-stage triple-negative breast cancer (TNBC) in this study. We retrospectively analysed a total of 257 early-stage TNBC patients treated at Sun Yat-sen University Cancer Center (SYSUCC) between March 2006 and October 2016. Their clinicopathological information and haematological data tested within one week of the diagnosis were collected. According to the IronMLR score cutoff value of 6.07µmol/L determined by maximally selected rank statistics, patients were stratified into the low- and high-IronMLR groups, after a median follow-up of 92.3 months (95% confidence interval [CI] 76.0-119.3 months), significant differences in 5-year disease-free survival (DFS) rate (81.2%, 95% CI 76.2%-86.5% vs 65.5%, 95% CI 50.3%-85.3%, P = 0.012) and 5-year overall survival (OS) rate (86.0%, 95% CI 81.6%-90.7% vs 65.5%, 95% CI 50.3%-85.3%, P = 0.011) were seen between two groups. Further multivariate Cox regression analysis revealed the IronMLR score as an independent predictor for DFS and OS, respectively, we then established a prognostic nomogram integrating the IronMLR score, T stage and N stage for individualized survival predictions. The prognostic model showed good predictive performance with a C-index of DFS 0.725 (95% CI 0.662-0.788) and OS 0.758 (95% CI 0.689-0.826), respectively. Besides, calibration curves for 1-, 3-, 5-DFS and OS represented satisfactory consistency between actual and nomogram predicted survival. In conclusion, the Iron-inflammation axis might be a potential prognostic biomarker of survival outcomes for patients with early-stage TNBC, prognostic nomograms based on it with good predictive performance might improve individualized survival predictions.